Provider insight on surmounting specialty practice challenges to improve Tdap immunization rates among pregnant women. Issue 5 (May 2018) - Mehrotra, Arpita; Fisher, Allison Kennedy; Mullen, Jennifer; Rodriguez, Leslie; Jiles, Angela J.; Albert, Alison P.; Randall, Laura A.; Frew, Paula M.
Abstract: Background: Pertussis, or "whooping cough, " is an acute, contagious pulmonary disease that, despite being vaccine-preventable, has become an increasingly widespread problem in the United States. As a result, the Advisory Committee on Immunization Practices and American College of Obstetricians and Gynecologists updated recommendations stating clinicians should give a Tdap dose during every pregnancy, preferably at 27–36 weeks. Despite this recommendation, reported Tdap vaccine receipt rates during pregnancy vary from 16–61%, and previous studies have shown that clinician recommendation and vaccine administration are strongly associated with vaccine uptake among pregnant women. Methods: Our aim was to inform new strategies to increase uptake of the Tdap vaccine among pregnant women and, ultimately, reduce pertussis-related morbidity and mortality in infants. We conducted interviews with a sample of 24 ob-gyns. We subsequently performed grounded theory analyses of transcripts using deductive and inductive coding strategies followed by intercoder reliability assessment. Results: All physicians interviewed were familiar with the most recent recommendation of giving the Tdap vaccine during the third trimester of every pregnancy, and the majority of physicians stated that they felt that the vaccine was important and effective due to the transfer of pertussis antibodies from the mother to the fetus. Most physicians indicated that they recommended the vaccine to patients during pregnancy, but not all reported administering it on site because it was not stocked at their practice. Implementation challenges for physicians included insurance reimbursement and other challenges (i.e., patient refusal). Tdap vaccination during pregnancy was a lower clinical priority for some physicians. Physicians recognized the benefits associated with Tdap vaccination during pregnancy. Conclusions: Findings indicate while most ob-gyns recognize the benefits of Tdap and recommend vaccination during pregnancy, barriers such as insurance reimbursement and financial concerns for the practice can outweigh the perceived benefits. This resulted in some ob-gyns reporting choosing not to stock and administer the vaccine in their practice. Recommendations to address these concerns include 1) structural support for Tdap vaccine administration in ob-gyns practices; 2) Continuing medical education-equivalent educational interventions that address management techniques, vaccine coding, and other relevant information; and 3) interventions to assist physicians in communicating the importance of Tdap vaccination during pregnancy.